Unusual caudal vena cava thrombosis in a cow, secondary to Trueperella (Arcanobacterium) pyogenes infection - Motta, Rodrigo Garcia [UNESP]; Motta, Igor Garcia; Martinez, Antonio Campanha; da Silva, Aristeu Vieira; Paes, Antonio Carlos [UNESP]; Martins, Lorrayne Souza Araujo; da Silva, Rodrigo Costa; Ribeiro, Marcio Garcia [UNESP] (FapUNIFESP (SciELO), 2016)
The caudal vena cava thrombosis, or pulmonary thromboembolism, in cattle is correlated with lactic acidosis, caused by diets rich in grains and highly fermentable, associated or not to septic situations, used in feedlots of beef or high-producing dairy cattle. This paper reports an unusual caudal vena cava thrombosis in a cow, secondary to Trueperella (Arcanobacterium) pyogenes infection, resulting in reduced milk production, anorexia, pale mucous membranes, ruminal atony, sternal decubitus and autoauscultation position. The heart was enlarged at necropsy, presence of clots distributed along the thoracic cavity, adherence between lung and pleura, abscesses, emphysema, petechiae, suffusions and ecchymosis in lungs, thickening of the caudal vena cava wall, hepatomegaly with chronic passive congestion (nutmeg aspect), and rumenitis. In lab, the actinomycete Trueperella (Arcanobacterium) pyogenes was isolated from liver and lung samples, probably resulting through dissemination of the bacteria of the rumen content, what reaffirms the opportunistic behavior of this actinomycete.
Keywords: Abscesses; Acidosis; Ruminants; Thromboembolism; Trueperella (Arcanobacterium) pyogenes